Parâmetros granulométricos e relações morfoestratigráficas dos depósitos sedimentares de vertente : o caso da Serra de São Pedro - Faxinal - PR - Sordi, Michael Vinicius (2013)
The present study traverse about the application of technics of faciological analysis in torrential flows deposits in hillslope. The study searches to understand how the superficial layers along the hillslopes of the north part of the Paranaense Second Plateau were formed through the study of a hillslope locate in the São Pedro river watershed. The area its located in the plateau edge, in the transition between the Second and the Third Paranaense Plateau, where outcrops igneous and sedimentary rocks of the Mesozoic and Paleozoic, characterized by high density of faults and fractures and a diabase dike swarm of NW-SE direction, coincident with the Ponta Grossa Arch axis. The study is based in on-site descriptions of the deposits, where were also obtained measurements of the biggest clasts e were collected samples for particle size analysis in laboratory. Also on-site, were realized a detail topographic survey through the Geodesic GPS Pro Mark 200. The studied hillslope shows 1.750 m length and an altimetric amplitude of 228,55m, in other words, a 0,13 m/m or 130 m/km gradient and a medium steepness of 13%. Initially the hillslope developed by downwearing process in a climate like the actual, however geological and geomorphologycal factors were responsible for differentiate sectors in this hillslope. Nowadays, the hillslope shows a complex running, with five baselines, that were subdivided, by its working in three compartments, videlicet: compartment 1 that characterizes by the sediment accumulation; the compartment 2, that's under influence of the diabase dyke and the compartments 3, 4 and 5, of the hollows. In the low hillslope dominate the sediment accumulation process, with thicker and older deposits. In the medium hillslope the diabase dyke influence yields soils and clay deposits. The high hillslope it's the more morphodinamically active compartment, where the sediments are being constantly remobilized and the deposits are thinner. The evolution of this hillslope remounts to the remote periods, when the rocks of Serra Geral e Botucatu formations still covered the hillslopes. Torrential flows were responsible for mobilize these sediments through the hillope, today restrict to rock fragments in the low hillslope facies and boulders over surface. Dyke influence is outstanding, mainly at medium and high hillslope, where concavities hollows attached to N-S normal fault zones made arise a series of baselines limited by drainage breaks that control the evolution of local modeling.